Energy Landscapes for Proteins: From Single Funnels to Multifunctional Systems. Issue 4 (8th January 2019) - Röder, Konstantin; Joseph, Jerelle A.; Husic, Brooke E.; Wales, David J.
Abstract: This report advances the hypothesis that multifunctional systems may be associated with multifunnel potential and free energy landscapes, with particular focus on biomolecules. It compares systems that exhibit single, double, and multiple competing structures, and contrasts multifunnel landscapes associated with misfolded amyloidogenic oligomers, which presumably do not arise as an evolutionary target. In this context, intrinsically disordered proteins could be considered intrinsically multifunctional molecules, associated with multifunnel landscapes. Potential energy landscape theory enables biomolecules to be treated in a common framework together with self‐organizing and multifunctional systems based on inorganic materials, atomic and molecular clusters, crystal polymorphs, and soft matter. Abstract : This report investigates the hypothesis that multifunctional systems are associated with multifunnel potential and free energy landscapes. The potential energy landscape approach is employed to show how biomolecules can be treated in a common framework, which is applicable throughout molecular science. For example, in designing a molecular switch, a double‐funnel landscape, with tunable stability between competing morphologies, is required.